Calculations in Agriculture the Need and Relevance of Legal Regulation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
the impact of the judicial system on Civil Relations related to the calculations of the subjects of, an event operating in the field of Agriculture, the specific aspects of the existing legal framework were studied. In solving issues of legal regulation of calculations in agriculture, proposals and recommendations were developed aimed at increasing the capabilities of the judicial system.